Periodic acid-schiff stain and p53 marker: reducing interobserver variability in microinvasive oral squamous cell carcinoma diagnosis - Rehan, Syeda Areeba; Parveen, Bushra; Ara, Nighat; Hafeez Ud Din; Rathore, Muhammad Usman; Muneer, Saadia (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the effectiveness of periodic acid-Schiff stain and p53 immunohistochemical marker in reducing interobserver variability for diagnosing microinvasive oral squamous cell carcinoma cases. Method: The cross-sectional study was conducted at a tertiary care diagnostic hospital in Rawalpindi, Pakistan, from March 31 to July 31, 2023, and comprised diagnostically challenging biopsy specimens. The specimens were subjected first to haematoxylin and eosin stain, and then with periodic acid-Schiff stain and tumour protein p53 immunohistochemistry simultaneously. A preliminary diagnosis on routine staining alone and a final diagnosis with the two adjuncts were reported by two observers who were both blinded to the prior diagnosis. Data was analysed using SPSS 25. Results: Of the 30 specimens diagnosed, 21 (70%) belonged to males and 9 (30%) to females. The mean age of the patients was 60.47±11.78 years. Periodic acid-Schiff staining and tumour protein p53 immunohistochemistry demonstrated a significant decrease in interobserver variability in the diagnosis of microinvasive oral squamous cell carcinoma, exhibiting enhanced visualisation in basement membrane breach and identifying the invading cells within the lamina propria that were masked on routine staining (p<0.05). Conclusion: Periodic acid-Schiff stain and tumour protein p53 immunohistochemistry could assist in reducing interobserver variability in the diagnosis of microinvasive oral squamous cell carcinoma. Key Words: Interobserver variability, Periodic acid-Schiff reaction, Oral squamous cell carcinoma, Immunohistochemistry.